Pemikiran Amina Wadud tentang Rekonstruksi Penafsiran Berbasis Metode Heurmeneutika - Ernita Dewi (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Hermeneutics has been known by Moslems since early twentieth century. As a method, it is used some Moslem scholars in interpreting the Quranic texts because it is regarded to give rational and creative way of interpreting religious texts. Together with the emerging terms of deconstruction, reconstruction and rationalization of religious texts, hermeneutics has become a favourite method to interprete the Qur’an. Anyhow, this method has not yet accepted by all Moslem ulamas just because it is regarded a non-Muslim method, it is a method used by Cristian bishops in interpreting Bible. Regardless its controversy, Amina Wadud, a female Muslim scholar, keeps using hermeneutics in interpreting quranic verses, mainly the verses relating female. According to her, the method is the most applicable one to interprete the Qur’an for the modern time.